2020
DOI: 10.1101/2020.02.20.958363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LSD1 represses a neonatal/reparative gene program in adult intestinal epithelium

Abstract: 30Intestinal epithelial homeostasis is maintained by adult intestinal stem cells, which, alongside 31 Paneth cells, appear after birth in the neonatal period. We aimed to identify new regulators of 32 neonatal intestinal epithelial development by testing a small library of epigenetic modifier 33 inhibitors in Paneth cell-skewed organoid cultures. We found that Lysine-specific 34 demethylase 1A (Kdm1a/Lsd1) is absolutely required for Paneth cell differentiation. Lsd1-35 deficient crypts, devoid of Paneth cells,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…Yui et al identified that YAP/TAZ-mediated reprogramming of intestinal epithelium into a repair state is important in this disease model (Yui et al, 2018), and we found that Lsd1-deficient epithelium matches the phenotype of reparative epithelium ( Fig. 1, and (Zwiggelaar et al, 2020). We thus wanted to test whether Lsd1-deficient epithelium would be protective upon inflammatory damage, like it is upon damage induced by irradiation.…”
Section: Lsd1 Is Protective During Chemically Induced Colitismentioning
confidence: 76%
See 4 more Smart Citations
“…Yui et al identified that YAP/TAZ-mediated reprogramming of intestinal epithelium into a repair state is important in this disease model (Yui et al, 2018), and we found that Lsd1-deficient epithelium matches the phenotype of reparative epithelium ( Fig. 1, and (Zwiggelaar et al, 2020). We thus wanted to test whether Lsd1-deficient epithelium would be protective upon inflammatory damage, like it is upon damage induced by irradiation.…”
Section: Lsd1 Is Protective During Chemically Induced Colitismentioning
confidence: 76%
“…LSD1 can demethylate mono or dimethylated Histone 3 Lysine 4 (H3K4me1/2) that normally mark active or poised enhancers (Shi et al, 2004). Importantly, we previously found that LSD1-deficient small intestinal epithelium is in a continuous state of repair (Zwiggelaar et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations